Ambivalent Attachment — Melancholia and Political Activism in Contemporary Palestine. (December 2016) - Segal, Lotte Buch
Abstract: This article argues that over the course of the past three decades a mood change has occurred in terms of how Palestinians relate to the ideal of an independent Palestinian state. During the first Intifada, from 1987 to 1993, which constitutes the golden age of Palestinian resistance towards Israel's occupation, the Palestinian resistance movement was characterized by a passionate belief in the possibility of a revolutionary transformation. Due to the consistent stalemate and even worsening of the conflict that have followed in the wake of the Second Intifada, from 2000 to 2003, this passionate belief in the realization of a Palestinian state has been replaced by ambivalence toward that ideal. Based on insights from my intermittent fieldwork with families of Palestinian political prisoners from 2004 to 2011, this article suggests that the contemporary ambivalence surrounding the revolutionary project can be meaningfully analyzed using Freud's notion of melancholia. In Freud, melancholia accounts for the relation between a feeling of indeterminate loss and ambivalent attachment. The notion of melancholia thereby provides anthropology with a concept that can be used to name and explore the frayed attachment to the ideal of a Palestinian state in the context of an ongoing colonial occupation. The passionate politics of the First Intifada enabled a fusing of Palestinian personhood with the overall political project into a subject characterized by active resistance. In contrast, the ambivalent attachment that marks the link between self and state project in the Palestinian territories after the Second Intifada leads to a mood of melancholia. By analyzing the attachment to the political project as an indeterminate loss in the melancholic's ego, I argue that the Palestinian political project is part of the self and keeps its adherents in a repetitive temporal fold from which they are unable to escape, because they are obliged and compelled to keep fighting for a state that does not seem to materialize. Conceptually, melancholia has the capacity to elucidate the emotional and deeply intersubjective toll it takes to live and aspire to an ideal that seems further from realization by the hour.